Association of Human Leukocyte Antigen (HLA) class II (DRB1 and DQB1) alleles and haplotypes with Rheumatoid Arthritis in Sudanese patients - Ali, Adil Ahmed; Khalid, Khalid Eltahir; Mohammed, Somaya Elhaj; Akhtar, Mohammed Salman; Saeed, Osman Khalafalla (Frontiers in Immunology, 2023)
The aim of this study was to determine the human leukocyte antigen (HLA) class  (DRB1 and DQB1) alleles and haplotype frequency of rheumatoid arthritis (RA) in the Sudanese population. The frequency of HLA-DRB1 and -DQB1 alleles and DRB1-DQB1 haplotypes were determined in 122 RA patients and 100 controls. HLA alleles were genotyped in low resolution by using the polymerase chain reaction-sequence specific primers (PCR-SSP) method. In RA patients, HLA-DRB1*04 and *10 alleles were high in frequency (9.6%, P = 0.038 and 14.2%, P = 0.042, respectively), and dependently on anti-citrullinated protein antibodies (ACPAs) seropositivity (P = 0.044 and P = 0.027, respectively). In contrast, the frequency of the HLA-DRB1*07 allele was significantly low (P = 0.010) in patients (5.0%) than in controls (11.7%). Moreover, HLA-DQB1*03 allele was strongly associated with RA risk (42.2%, P = 2.2x10-8), whereas, HLA-DQB1*02 and *06 showed protective effects against RA (23.1%, P = 0.024 and 42.2%, P = 2.2x10-6, respectively). Five different HLA haplotypes, (DRB1*03-DQB1*03, DRB1*04-DQB1*03, DRB1*08-DQB1*03, DRB1*13-DQB1*02, and DRB1*13-DQB1*03) were significantly associated with RA risk (P = 0.00003, P = 0.00014, P = 0.027, P = 0.004, and P = 3.79x10-8, respectively), while 3 protective haplotypes (DRB1*03-DQB1*02, DRB1*07-DQB1*02, and DRB1*13-DQB1*06) were identified (P = 0.004, Pc = 0.002, and P = 0.01, respectively). This is the first study determining the association between HLA class  patterns and RA risk in our population.